Otra mirada a la responsabilidad del Estado frente al lavado de activos y la captación masiva y habitual de dineros del público (2018)
A critical reflection is exposed with regards to the responsibility of the Colombian State in the surveillance, control and action that it must carry out, from the administrative field, in relation to the practices of money laundering and massive and habitual collection of money from the perspective of the omission and legitimate expectation.